2. OPTIMIZING HUMAN RESOURCE MANAGEMENTAS A QUALITY IMPROVEMENT STRATE - Neisha Kurnia Damayanti; Habbi Firlana; Pascalis Danny Kristi Wibowo; Nur Priyanto; Suroso; Anwar Hendro; Tutidikatama; Farrid Hidayat (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to analyze the optimization of human resource management asa strategy to enhance the quality of immigration public services. Human resource managementplays a crucial role in improving public service quality, particularly in immigration services,which demand precision, responsiveness, professionalism, and public trust. Immigrationservices involve not only administrative procedures but also legal certainty, document security,public mobility, and the nation's image in serving both citizens and foreign nationals. This studyemploys a descriptive qualitative approach through a literature review, examining relevant priorresearch on human resource management, employee competence, public service quality,digital service innovation, workload, and immigration services. The findings indicate that thequality of immigration public services is significantly influenced by employee competence, workdiscipline, professionalism, integrity, workload management, and employee readiness to adaptto digital-based services. Human resource optimization can be achieved through competencedevelopment, continuous training, appropriate personnel placement, workload evaluation, thestrengthening of a service culture, and the enhancement of digital literacy. The studyrecommends that immigration agencies prioritize human resource development as a strategicelement of public service reform. Robust human resource management can facilitateimmigration services that are faster, transparent, responsive, and oriented toward publicneeds.